(untitled) (Eurasian Journal of Philology Science and Education, 2016)
The article deals with the complexity and multiple meaning of the great Kazakh writer M.Auezov’s early prose. The question about the dialogue of philosophical motifs in the early works of M.Auezov gives effectual help to see the deepest currents of his thoughts. The unity of man and the world, given to him primarily in the direct sense is one of the main themes of the early prose of the writer, where existential posing of some problems is noticeable. «The fate of the defenceless», «The orphan», « Steppe sketches» and other stories should be also studied in this regard. Event, action, emotion of these stories are often secondary since primary are thought, its almost autonomous life, the artist’s intention and the idea of the hero, often modeled as a situation.